EasyBranding : herramienta que facilita la creación o redefinición de branding sensorial basada en el módulo Innovación en Branding. (2020)
Purpose - Help people who do not have specific knowledge in branding and need or want to create or redefine a brand. This, through a digital and physical tool that allows them to understand, devise and define the essence of the brand through sensory components. Design/methodology/approach - This research is determined by the double diamond process. First, a problem was found in the "Innovation in Branding" module of the Master in Innovation Management at Universidad Icesi. Following this, a theoretical investigation was carried out parallel to the field work and with the results of these, the prototype was proposed which was validated and iterated for better results. Findings - The solution proposal facilitates and optimizes processes that allow understanding, devising and defining a brand through sensory components. Thanks to its digital interaction that implements gamification as a complement to a physical sensory kit, the proposed interaction motivates people to carry out these processes and to transmit the essence of their brand in a more consistent way.